Green Marketing of Productive Waqf: A Marketing Strategy Based on Maslahah and Sustainable Development - Ermi Herawati (International Journal of Sharia Business Management, 2026)
This study aims to analyze the concept and implementation of green marketing in the management of productive waqf as a marketing strategy based on maslahah and sustainable development. It also seeks to identify how the integration of environmental, social, and economic sustainability values in productive waqf can enhance public trust and expand the participation of waqif in the development of the Islamic economy. The research employs a qualitative method with a literature study and conceptual analysis approach. Data were collected from various sources such as scientific journals, books, waqf institution reports, and related documents on green marketing, productive waqf, and sustainable development. The data analysis technique used descriptive analysis and a normative-conceptual approach to examine the relationship between the principles of green marketing, the concept of maslahah in Islamic economics, and the practices of productive waqf management. The results show that the implementation of green marketing strategies in productive waqf can be carried out through several approaches, including transparency in waqf fund management, promotion based on sustainability values, utilization of waqf assets for environmentally friendly activities, and the use of digital media to increase public awareness of the importance of waqf that generates social and ecological impact. The integration of the concept of maslahah in marketing strategies also strengthens sharia legitimacy and encourages the creation of long-term benefits for society and the environment.